The Rio Branco Declaration: Assessing Progress Toward a Near-Term Voluntary Deforestation Reduction Target in Subnational Jurisdictions Across the Tropics - Stickler, Claudia; David, Olivia; Chan, Charlotta; Ardila, Juan Pablo; Bezerra, Tathiana (Frontiers in Forests and Global Change, 2020)
Voluntary commitments are playing an ever-greater role in environmental governance at all scales. In the years preceding the signing of the Paris Agreement in 2015, a flurry of non-state and state actors signed on to various declarations and commitments to reduce deforestation as one globally significant climate mitigation solution. This paper focuses on the Rio Branco Declaration (RBD) and the 30 first-order subnational jurisdictions located in Brazil, Indonesia, Mexico, and Peru that signed on to it between 2014 and 2018, committing to reduce deforestation 80% by 2020, conditional upon adequate financial support from the international community. We assess each study jurisdiction’s progress toward that commitment based on deforestation data, and examine some of the potential factors supporting or slowing progress, including the existence of commensurate targets within jurisdictions’ legal frameworks and the international financial support pledged to jurisdictions. We found that progress toward achieving the target was slow and likely unattainable in most jurisdictions outside of Brazil. Among the four jurisdictions likely to achieve the target under current deforestation trajectories, only Mato Grosso has a target within its legal framework that is more ambitious than the RBD target. We found that the international response to the RBD was sluggish and likely inadequate – with only one financial pledge made in direct response to the declaration and the majority of funding to support jurisdictional efforts coming from one source. We did not find a clear relationship between international finance pledged and progress toward the RBD deforestation target; however, more often, jurisdictions that received pledges earlier have made more progress. We explore what may explain individual jurisdictions’ performance with respect to the target, including specific jurisdictional circumstances, national context, and international support. We estimate that, if current deforestation trajectories continue, the RBD signatories in our study could contribute approximately 3.7% (0.65 GtCO2e) of the greenhouse gas emissions reduction needed to keep global warming at 1.5°C, compared with a potential 5.7% (0.98 GtCO2e) if they were to all meet the RBD target.